ANALISIS SEKUEN INTRON 1 SAMPAI SEBAGIAN EKSON 4 DARI GEN FERITIN2 PADA TIGA GENOTIPE PADI (Oryza sativa L.) LOKAL INDRAGIRI HILIR, RIAU - Herman Herman; Yolla Putri Ardila; Fadel Nugraha; Dewi Indriyani Roslim (UIR Press, 2014)
Iron toxicity is one of the limiting factors of rice crop production in lowland area. Iron homeostasis in cell involves the role of ferritin protein. The objective of this study is to analyze potion of first intron to fourth exon sequence of local rice varieties from Indragiri Hilir, Riau Province. Plant material were three local rice genotype, namely Bakung, Siputih, and Serei, and two rice varieties consisted of IR64 (Fe toxicity-sensitive rice variety) and Siam Sintanur (Fe toxicity-tolerant rice variety). Methods include DNA isolation, PCR (Polymerase Chain Reaction), electrophoreses, and sequencing. The DNA sequence was analyzed using BLASTn and ClustalW2 programs. This research got DNA fragments of ferritin2 gene sizing of about 850 bp, 1200 bp, and 1500 bp. Sequence analysis of the 1200 bp DNA fragment showed the presence of 49 SNPs scattered portion of first intron to fourth exon. Bakung rice genotype had very close proximity to Siam Sintanur and Nipponbare compared with IR64, while Serei and Siputih rice genotypes had a great distance to Siam Sintanur and Nipponbare. The result concluded that Bakung rice genotype may be more tolerant to Fe-toxicity than Siputih and Serei.